275 million migraine sufferers without preventive treatment worldwide: distribution among gbd superregions: English - Liger, Ivy (2024)
Background Migraine is a prevalent neurological disease impacting around one billion people globally. According to the Global Burden of Diseases 2021, it is the third leading cause of disability among central nervous system disorders. Despite its significant impact, there are substantial gaps in the optimal management of preventive migraine therapy within global health systems. Objective The objective of this study was to review the patterns of access to healthcare treatment for preventive migraine medication among individuals diagnosed with migraine in various GBD regions. Methods A search of PubMed for articles published between January 1, 2000, and June 25, 2024, was conducted. Studies included those that reported on healthcare resource utilization, treatment access, unmet needs, and undertreatment of migraines. The American Headache Society (AHS) 2021 Consensus Statement algorithm was used to determine candidacy for preventive treatment. Results Out of 587 publications retrieved, 80 met the inclusion criteria. These included 56 from High-Income regions, 14 from South-East Asia, East Asia, and Oceania, 4 from Central Europe, Eastern Europe & Central Asia, 2 from Sub-Saharan Africa, 1 from Latin America & Caribbean, 1 from South Asia, and 2 from North Africa & Middle East. The prevalence of preventive treatment in the migraine population ranged from 0% in Nigeria to 36.2% in Japan, with a global 1-year-age adjusted prevalence of 17.8%. Based on the AHS consensus statement algorithm, approximately 38.7% of the global migraine population would qualify for preventive treatment. However, around 79.8% of these candidates are not receiving preventive treatment, equating to approximately 275 million people globally. Conclusions There are significant gaps and a lack of recent information in the literature regarding the preventive treatment of migraines. More recent, population-based studies are necessary to assess the recognition of migraine preventive candidates and those undergoing preventive treatment, to inform better public health strategies for migraine diagnosis and treatment.   This research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors.